The Summers readers: primer - Summers, Maud; Perkins, Lucy Fitch, 1865-1937 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Summers Readers: Primer" by Maud Summers is a children's educational book published in the early 20th century. This primer serves as an introductory text designed to engage young readers with rhymes, poems, and simple stories, focusing on themes such as nature, family, and everyday activities. The book consists of various short verses and action sentences aimed at helping children develop reading skills while encouraging participation through playful language and rhythmic patterns. It includes familiar nursery rhymes like "Rock-a-Bye Baby" and "Hickory Dickory Dock," along with engaging narratives about common life events, such as farming and play. Each section is enriched with illustrations, creating an interactive learning experience for young readers and fostering a love for reading from an early age. (This is an automatically generated summary.)
Rhymes and poems.
Release date is 2022-07-03
hekula03 and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Readers (Primary)